The BDNF Val66Met Polymorphism, Regular Exercise, and Cognition: A Systematic Review. (August 2020) - Liu, Tingting; Li, Hongjin; Colton, Joseph P.; Ge, Song; Li, Changwei
The purpose of this study was to synthesize research evidence from studies on the relationships among the BDNF Val66Met polymorphism, regular exercise, and cognition in human subjects. PubMed, CINAHL, and Web of Science were searched systematically. Search limiters applied in these databases included humans, English language, time limits from 2009 to 2019, and peer-reviewed journal articles. Eight studies were included in the current review. While there was some evidence to tentatively suggest that greater levels of exercise were associated with certain forms of memory in Val/Val homozygotes than Met carriers, more research is needed to corroborate these findings. Regarding attention/information processing speed, executive function as well as global cognition, the evidence is either inconsistent or sparse and does not allow for tentative conclusions. Compelling evidence from high-quality clinical trials is needed to re-examine the relationship between the BDNF Val66Met polymorphism, exercise, and cognition.